Effect of HIV, antiretrovirals, and genetics on methadone pharmacokinetics: Results from the methadone antiretroviral pharmacokinetics study. (1st October 2021) - Bart, Gavin; Giang, Le Minh; Yen, Hoang; Hodges, James S.; Brundage, Richard C.
Highlights: HIV increase methadone clearance and volume of distribution by 25%–35%. Antiretrovirals increase R- and S-methadone clearance 220% and 400%, respectively. NR1I3 variants increased R-and S-methadone clearance 20% in those taking efavirenz. ABCB1 variants impacted R-methadone clearance by 10%. The CYP 2B6*4 variant decreased S-methadone clearance by nearly 20%. Abstract: Background: Methadone treatment of opioid use disorder in HIV-infected individuals is complicated by drug-drug interactions. Genetic and other cofactors further contribute to interindividual variability in methadone pharmacokinetics. We used population pharmacokinetics to estimate the effect of drug-drug interactions, genetics, and other cofactors on methadone pharmacokinetics in a methadone maintained population in Vietnam. Methods: Plasma R- and S-methadone levels were measured in 309 methadone maintained individuals just before and 2−5 h following methadone dosing. A linear one-compartment population pharmacokinetic model with first-order conditional estimation with interaction was used to evaluate methadone clearance (CL/F) and volume of distribution (V/F). The influence of covariates on parameter estimates was evaluated using stepwise covariate modeling. Covariates included HIV status, antiretroviral use (efavirenz or nevirapine), weight, BMI, age, methadone dose, and 8 single nucleotide polymorphisms in across the CYP2B6, ABCB1, and NR1I3 genes. Results: Taking either efavirenz or nevirapine increased R-methadone CL/F 220%. Nevirapine and efavirenz increased S-methadone CL/F by 404% and 273%, respectively. Variants in NR1I3 increased R- and S-methadone CL/F by approximately 20% only in patients taking efavirenz. Different alleles in ABCB1 rs2032582 either increased or decreased R-methadone CL/F by 10%. The CYP 2B6*4 variant decreased S-methadone CL/F by 18%. HIV-infection increased R- and S-methadone CL/F and V/F by 24%–39%. Conclusions: The HIV antiretrovirals nevirapine and efavirenz significantly increase methadone clearance. Variants in NR1I3 increased the effect of efavirenz on methadone clearance. Other variants affecting methadone CL/F were also confirmed. To our knowledge, this is the first report of HIV itself affecting methadone pharmacokinetics.